Fibroin and Spidroin Thin Film to Support the Attachment and Spread of Human Dermal Fibroblast: The Potency of Skin Tissue Engineering - Safira Meidina Nursatya; Anggraini Barlian; Hermawan Judawisastra; Indra Wibowo; Hutomo Tanoto (Journal of Mathematical and Fundamental Sciences, 2021)
This study aimed to determine the characteristics of scaffolds made of fibroin from Bombyx mori and spidroin from Argiope appensa in supporting the attachment and proliferation of HDF cells on the scaffolds. Thin-film scaffolds were made using the solvent casting technique, where the scaffold is an amalgamation of fibroin, spidroin, PVA, and glycerol. HDF cells were grown on DMEM medium with 10% FBS and 1% antibiotic-antimicotic. Characterization of the scaffolds was performed by using ATR-FTIR, swelling test, contact angle measurement, tensile test, biodegradation, MTT and SEM. The results of the ATR-FTIR analysis showed that the scaffolds contained fibroin, spidroin, PVA, and glycerol. Swelling and contact angle tests showed that all scaffold combinations were hydrophilic. Mechanical properties and in vitro biodegradation tests showed no significant difference among the scaffold combinations. MTT testing showed that all scaffolds could facilitate the attachment of fibroblasts and showed increased viability from day 1, 3, and 5. Scanning electron microscopy showed that the cells in the 70% fibroin and 10% spidroin scaffold had the best cell morphology and the best combination for potential application in skin tissue engineering.